Molecular relaxation of components of LC mixture 2f- 3333 (ROLIC) for dual- frequency electrooptic shutters. Issue 12 (26th September 2019) - Rybakov, D. O.; Belyaev, V. V.; Kumar, S.; Chigrinov, V. G.; Zhachkin, V. A.
ABSTRACT: Dual-frequency liquid crystal materials are used in fast response electrooptic modulators in different devices for digital information displaying and processing. In an NLC mixture 2f-3333 (ROLIC, Switzerland) there are components with lateral dipole moment. Their molecular relaxation is investigated by a method of dielectric spectroscopy. Values of relaxation time and its activation energy, molecular friction coefficient, rotational diffusion are obtained. They are compared with data obtained by other methods like LC viscosimetry. Graphical Abstract: